Viacrozmerná analýza populačného starnutia v okresoch Slovenska v rokoch 2011 a 2021 - Marcela Káčerová; Dagmar Kusendová; Iveta Stankovičová (Demografie)
Population ageing is a typical feature of population development in the majority of countries in the world. In each population, this process is specific –whether in terms of the timing of its onset or the factors that modify the process of population ageing. The main aim of this article is to identify the processes of population ageing in the districts of Slovakia. A regional analysis of this process focused on population ageing in Slovak districts in the years 2011 and 2021 using cluster analysis. The results of the cluster analysis of population ageing identified northern and eastern Slovakia as districts whose populations have a younger age structure. The western and southwestern districts of Slovakia have populations with an old age structure. In 2021, this age polarity began to change the territory of Slovakia. The suburbanised region of the capital, Bratislava, is becoming significant, as the population in the districts there is getting younger.